Crowding causes detachment and loss of mobile sea lice: Fine-meshed crowding nets may mitigate spread - Lena Geitung; Luke T. Barrett; Velimir Nola; Sussie Dalvin; Line Vatne Martinsen; Adele Dahlgren; Frode Oppedal (Aquaculture Reports)
Detachment of mobile lice from salmon during crowding and handling procedures in sea-cage fish farms may lead to loss and unwanted spread of ectoparasitic sea lice to other cages, farms or wild fish. However, rates of detachment and loss of lice during crowding are not well understood. We conducted a series of replicate crowding events in 125–2000 m3 sea-cages, using either a standard coarse-meshed crowding net, or a more fine-meshed crowding net intended to retain detached mobile lice. Lice that were detached during crowding and passed through the crowding net were collected using a 350-µm plankton net positioned around the crowding net (in some cases pumps and filters were also used), allowing lice ‘lost’ from the crowding net to be directly quantified. Detachment of lice during crowding varied from 2 % to 38 %, with higher detachment rates for smaller life stages (highest for pre-adult 1 salmon lice) and in trials involving larger fish and/or longer crowding durations (up to 2 h). In most cases, the type of crowding net did not affect detachment rates, but the fine-meshed crowding net did retain some detached lice, including 75 % of adult female salmon lice. The fine-meshed crowding net also improved welfare outcomes for crowded fish, including significantly reduced scale loss, fin damage and bleeding. Provided dissolved oxygen levels can be maintained, fine-meshed crowding nets may be the most promising means of limiting the spread of mobile lice into the surrounding environment, while also reducing injuries to fish. Supplementary benefits may be achieved by minimising crowding time but also ensuring filter collection on the water used to bring fish into wellboats and delousing systems.